Uso de métodos heurísticos e branch-and-bound para otimização do layout fabril da linha de montagem de um componente automotivo na região de Curitiba - Balau, Adriano Pereira (2013)
Nowadays, the manufacturing enterprises are constantly looking for costs reduction, driven by rivalry and competition, which are strong globalization characteristics. In the Toyota Production System (OHNO, 1988), are highlighted the seven wastes which can exist in a manufacturing process and that, consequently, generate costs to the product without, however, adding value to it. Some commonly found wastes are the work-in-process (WIP), raw material or finished products flow wastes. The layout study aims to optimize the layout of facilities inside a process to minimize, among others, the materials flow. This study aims to present a real case of a huge auto parts manufacturer enterprise located in Curitiba, PR, which spends millions a year on layout changes. The object of study is the assembly line of a specifical component that this company manufactures. Using Heuristic methods, it proposes an approach for the layout optimizing of this assembly line. This approach was divided in two stages: in the first one, the cell formation problem (in order to improve the computational time, as well as the solution quality) was solved in order to associate machines to parts. In the second stage, the layout optimizing problem is solved, considering the combination of machines to parts (made in first stage). In both stages the hybrid meta-heuristics approach (tabu search), as well as the Exact method so called Branch-and-Bound (this on first stage), were tested to solve this problem. The results found on layout of facilities were quite promising.